Multimorbidity and associated factors in the adult Indigenous population living in villages in the municipality of Aracruz, Espírito Santo, State, Brazil - Hully Cantão dos Santos; José Geraldo Mill (Cadernos de Saúde Pública)
Multimorbidity is associated with negative effects on the health of individuals, increasing the complexity of health care. This study aimed to determine the prevalence of multimorbidity and associated factors in the adult Indigenous population living in villages in Aracruz, Espírito Santo State, Brazil. This is a cross-sectional study using data from the project called Assessment of the Prevalence and Severity of Chronic Diseases in the Indigenous Population of Espírito Santo State. Data were collected from 2020 to 2022. Multimorbidity was defined as the presence of two or more chronic morbidities in a group of eight morbidities. As a measure of association, the prevalence ratio (PR) and its 95% confidence interval (95%CI), calculated by Poisson regression with robust variance, in crude models and models adjusted for covariates were used. The prevalence of multimorbidity was 52.1% (95%CI: 49.1-55.2), being significantly higher among women (PR = 1.47; 95%CI: 1.29-1.67), those aged ≥ 40 years (40-59 years: PR = 1.49; 95%CI: 1.28-1.73; ≥ 60 years: PR = 1.85; 95%CI: 1.55-2.20) and lower for individuals with higher education (PR = 0.65; 95%CI: 0.47-0.89). The prevalence of multimorbidity in the Indigenous population living in villages in Espírito Santo State was higher than that found in other studies in the general Brazilian population. There was association between the presence of multimorbidity and sex, age and education level.